Beauty and the beast - Palin, Cherly (London York press, 2020)
I am going on a trip, says beauty's father Jack , what present would you like? i'd like a rose, please says beauth, Jack sees a rose tree in the garden of a castle and he picks a rose for beauty. but it is the beast's castle and the beast is angry . bring your daughter here, says the beast , she must live here in the castle with me
English stories
1
Keywords: English stories